Terminated for Reasons of Taste : Other Ways to Hear Essential and Inessential Music - Eddy, Chuck (Book collections on Project MUSE., 2016)
In Terminated for Reasons of Taste, veteran rock critic Chuck Eddy brings lost, ignored, and maligned pop music to the fore, considering marginalized styles and artists right alongside pop music's heavyweights like Bruce Springsteen, the Beastie Boys, and Taylor Swift.